The Financial Cost of Carbon. Issue 2 (11th June 2022) - Bolton, Patrick; Halem, Zachery; Kacperczyk, Marcin
Abstract : Climate finance is first and foremost a risk‐management problem, which means three things for investors. First, prudent investors will seek to hedge climate change risk by reducing their exposure to this risk. Second, investors will demand compensation for holding this risk. Third, investors will engage with companies to urge them to reduce this risk if they are not adequately compensated for it. For companies, the main implication of climate‐risk management by investors is that the companies with greater carbon emissions will have to pay a higher financial cost of carbon (FCC). In their new study described in this article, the authors undertake a comprehensive analysis of the risk compensation implications of exposing investors to carbon transition risk. They explore how corporate GHG emissions have affected the price‐to‐earnings (P/E) ratios of listed companies in Europe and the U.S. over the period 2016 to 2020. Their main finding is that financial markets are beginning to broadly discount companies whose high carbon emissions are viewed as subjecting them to higher levels of political and regulatory risk, and providing them with what amounts to a higher cost of capital. Although price‐earnings ratios are generally lower for companies with higher emissions, the discount varies significantly by sector and across firm size, with larger companies experiencing the larger discounts. Although the carbon discount is similar in the U.S. and in Europe, the authors find significantly higher discounts in industries in Europe that are directly covered by carbon pricing through the EU ETS. They even find a small price discount on corporate debt for smaller issuers. Overall, what emerges is a clear pattern of investors' growing concern over climate risk, which translates into an increasingly material FCC for companies with high GHG emissions. This growing valuation discount for companies with high emissions should encourage them to progress further along their decarbonization path, which our results suggest have large financial as well as other social benefits.